The Development of Canadian-American Trade Union Relations: Some Conclusions - Williams, C. (Relations industrielles / Industrial Relations, 1966)
On one hand, binational trade unionism seems to be the product of three features in Canadian-American economic relations: international trade, labor migration and American investments in Canada. On the other hand, the origin of Canadian unionism and conflicts within can be explained by economic nationalism, by a commitment to the teachings of the Church in Québec and by an opposition to the AFL-type of craft unionism outside Québec. The boundary issue is irrelevant to the explanation of both phenomenas. In this article, the author has gathered some evidence which tends to support those hypotheses.